2018
DOI: 10.4103/1735-3327.231863
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness of different esthetic restorative materials: Evaluation and comparison after exposure to acidic drink

Abstract: Background:Acidic beverages, such as soft drinks (orange juice and cola), can produce erosion of resin composites. The aim of this in vitro study was to evaluate the effect of immersion in acidic drink on the Vickers microhardness (VK) of different esthetic restorative materials (one nanohybrid Ormocer-based composite, one nanoceramic composite, one nanofilled composite, and one microfilled hybrid composite).Materials and Methods:In this in vitro study, thirty specimens of each esthetic restorative material we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 27 publications
1
37
1
6
Order By: Relevance
“…10 In this study, higher surface microhardness was demonstrated by nanohybrid ormocer-based composite (Admira Fusion, Voco, Cuxhaven, Germany) compared to nanoceramic composite (Ceram X Universal) and Glasiosite compomer (VOCO). Unlike the results obtained by this study, Poggio et al 11 found an initial hardness of 57 HV associated with nanoceramic composite (Ceram X Universal) (less than this study, and the initial values of Admira); however, it can avoid acid attack effectively. Lastly, good initial value of microhardness was shown by the nanohybrid ormocer-based composite (Admira Fusion) and it did not display a significant loss of microhardness after being soaked in soft drink for a week.…”
Section: Discussioncontrasting
confidence: 99%
“…10 In this study, higher surface microhardness was demonstrated by nanohybrid ormocer-based composite (Admira Fusion, Voco, Cuxhaven, Germany) compared to nanoceramic composite (Ceram X Universal) and Glasiosite compomer (VOCO). Unlike the results obtained by this study, Poggio et al 11 found an initial hardness of 57 HV associated with nanoceramic composite (Ceram X Universal) (less than this study, and the initial values of Admira); however, it can avoid acid attack effectively. Lastly, good initial value of microhardness was shown by the nanohybrid ormocer-based composite (Admira Fusion) and it did not display a significant loss of microhardness after being soaked in soft drink for a week.…”
Section: Discussioncontrasting
confidence: 99%
“…Karaman et al [22] reported a decrease in microhardness of Filtek Supreme XTE TM after a 15-day challenge with Coke ® , as well as Gupta et al [23], who reported a decrease in microhardness of different restorative materials (composites, compomers and glass ionomers) after a 10 min/day immersion in Coke ® for 56 days. Poggio et al [24] also immersed four different composites in Coke ® and orange juice for 1 and 7 days, and a significant decrease in microhardness was also registered for all the groups. Silva et al [4] tested the effect of three different alcoholic beverages on three composite resin materials and also reported a decrease in microhardness after a 30 day immersion in beer.…”
Section: Discussionmentioning
confidence: 97%
“…when modified, has consequences such as: lower mechanical resistance, increased roughness, biofilm accumulation, surface degradation and marginal infiltration, which also supports the importance of studies evaluating the acid challenge in the resin load, as it is directly associated with mechanical properties [4,[6][7][8][9][10][11]. The aim of this study was to evaluate whether the inorganic content of a nanoparticulate composite resin solubilizes in the face of the acid challenge of two similar pH energy drinks, at different immersion times.…”
mentioning
confidence: 70%
“…The hydrophilic characteristics of the resin matrix influence the degree of water sorption and, therefore, acidic drinks can impair the surface integrity of the composite resins, aesthetically and physically, tending to cause erosion on the surface of material, and this degradation is related to the content and distribution of inorganic fillers [2,3]. Energy drinks are widely consumed, mainly by athletes, to promote well-being and better physical performance, due to the presence of components such as coffee, taurine and glucuronolactone [4][5][6]. However, the presence of citric acid, high sugar content and low pH of its composition are harmful to teeth and restorations, if consumed routinely [6,7].…”
Section: Introductionmentioning
confidence: 99%